Forage, freedom of movement, and social interactions remain essential fundamentals for the welfare of high-level sport horses - Phelipon, Romane; Hennes, Noémie; Ruet, Alice; Bret-Morel, Alexia; Górecka-Bruzda, Aleksandra; Lansade, Léa (Frontiers in Veterinary Science, 2024)
Societal concerns for animal welfare extend to all domestic species, including high-level sport horses. The welfare of these horses, notably highlighted during the recent Olympics, has garnered significant public interest, prompting inquiries into their living conditions. Animal welfare studies have emphasised three key needs crucial to equine welfare: unlimited access to forage, freedom of movement, and social interactions with peers, commonly referred to as the “3Fs”—access to Forage, Freedom of movement, and interactions with Friend conspecifics. However, the feasibility and benefits of satisfying these needs specifically for sport horses remain unexplored. Indeed, they may face unique challenges such as high physical workload, extensive travel, limited time in their home stables, weight management, and high economic value necessitating careful handling. Consequently, restrictions on feeding, freedom of movement, and social contact are often deemed necessary. This field study aims to assess the actual level of implementation of welfare in high-level sport horses by evaluating body condition, injury risk, and behavioural welfare indicators in their home stable. To achieve this objective, the welfare of 56 high-level sport horses competing internationally was assessed using behavioural indicators of welfare through scan sampling (abnormal behaviours, i.e., stereotypies, aggression towards humans, withdrawn behaviour, and alert behaviours; positions of the ears in a backward position while foraging, watching behaviours, and through other Animal Welfare Indicators (AWIN) protocol measures). This study shows that there exists a large variability among horses regarding their access to the 3Fs, with some of them having a lot of restrictions and others not, meaning it is possible to respect them while competing at a high level. Second, we observed that the fewer restrictions the horses experience regarding the 3Fs while in their home stables, the better their welfare, as demonstrated by the indicators we assessed. These results undeniably support the fact that unrestricted access to forage, the ability to move freely outdoors, and the opportunity to interact socially with conspecifics are fundamental needs of horses that could be provided to horses, also to high-performance ones. It is therefore essential that solutions are put in place to ensure that these conditions are met.